2011
DOI: 10.1161/circgenetics.110.958934
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Identity by Descent Mapping Uncovers the Genetic Basis for Blood Pressure Differences Between Spontaneously Hypertensive Rat Lines

Abstract: Background The recent development of a large panel of genome-wide single nucleotide polymorphisms (SNPs) provides the opportunity to examine genetic relationships between distinct SHR lines that share hypertension, but differ in their susceptibility to hypertensive end-organ disease. Methods and Results We compared genotypes at nearly 10,000 SNPs obtained for the hypertension end-organ injury-susceptible SHR-A3 (SHRSP, SHR-stroke prone) line and the injury-resistant SHR-B2 line. This revealed that that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 33 publications
(32 reference statements)
1
46
1
Order By: Relevance
“…The origin of these inbred lines has been previously reported 2, 9 . Animals were housed in an AAALAC-approved animal facility and provided a standard rodent chow diet and drinking water ad libitum.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…The origin of these inbred lines has been previously reported 2, 9 . Animals were housed in an AAALAC-approved animal facility and provided a standard rodent chow diet and drinking water ad libitum.…”
Section: Methodsmentioning
confidence: 98%
“…The two lines are derived from a single pair of founders common to both lines 11 . The ~87% of the genome shared identical by descent (IBD) across these lines is partitioned into discrete haplotype blocks 9 . SHR-A3 (males) and SHR-B2 (females) were crossed to generate an F1 progeny.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus expected that these strains will share the same alleles in much of their genome. Doris and his colleagues 23 used such identity-by-decent areas to exclude the genomic regions that do not contribute to BP differences between SHR/B2 and SHRSP/A3. Combining the identity-by-decent information with a QTL analysis, they identified a small non-identity-by-decent area on Chr 17, which could harbor a gene (or genes) contributing to the BP difference between the two strains.…”
Section: Genetic Studies On Hypertension and Cerebral Stroke In Shrspmentioning
confidence: 99%
“…On the basis of comprehensive gene expression data, they further suggested that Slc34a1, a sodium/phosphate co-transporter expressed in renal tubules, was a candidate gene. 23 This is a unique strategy in that they took advantage of the common genetic backgrounds shared between SHR and SHRSP.…”
Section: Genetic Studies On Hypertension and Cerebral Stroke In Shrspmentioning
confidence: 99%